2013
DOI: 10.5402/2013/137895
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Endoscopic Savary-Gillaard Bougies Dilation in Moroccan Plummer-Vinson Syndrome Patients

Abstract: e authors aimed to better de�ne the clinical, biological, radiological, endoscopic, and evolutionary characteristics of patients presenting with Plummer-Vinson syndrome aer endoscopic dilation and medical treatment in this study. ere were 41 cases of Plummer-Vinson syndrome listed. All these patients presented dysphagia associated to anemia, and all have bene�ted endoscopic dilation and iron supplementation with a good clinical and biological course in 100% of cases. e Plummer-Vinson syndrome is a rare ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The webs can be dilated using Savary-Guilard dilators [9] or TTS Balloon [4]. Choice depends on available dilators and infrastructure facilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The webs can be dilated using Savary-Guilard dilators [9] or TTS Balloon [4]. Choice depends on available dilators and infrastructure facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Other disorders reported to be associated with this syndrome include Celiac disease, Crohn's disease, Rheumatoid arthritis and thyroid disease raising the possibility immune dysregulation may be involved in its pathogenesis although this remains to be proven [7,8]. The web is typically eccentric, located in post-cricoid esophagus can get ruptured unintentionally during diagnostic endoscopy if it is very thin or can be ruptured using variety of dilatation techniques using Savary Guilard dilators, TTS balloons, or electro-cautery [4,9,10]. For the first time, we report a purposeful use of the endoscope for rupturing the web.…”
Section: Introductionmentioning
confidence: 99%
“…of patients with PVS, and thus it has been suggested that yearly endoscopic controls should be performed for such patients [15,16]. Tissue iron plays a vital role in the propagation of epithelial cells.…”
Section: What Should the Clinician Ask Him/herself Or The Patient? Y mentioning
confidence: 99%
“…The decline in reports and incidence of the syndrome may be related to the improvement in nutritional status and better treatment of iron deficiency (9). In Turkey, however, many Plummer-Vinson syndrome cases are still being reported (10,13,14). …”
mentioning
confidence: 99%